Analysis of the rheological behavior of polymer modified asphalt binders subjected to force-ductility test - Słowik, Mieczysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The basic measurement method used to assess the properties of polymer modified bitumens is a tensile test. In this study, PMB specimens of various elastomer SBS content (in the range from 3% to 9%), but a similar penetration, determined at 25°C were tested. In order to evaluate the rheological properties and temperature susceptibility, the Force-Ductility Tests were conducted at 0, 10 and 25°C. On the basis of the obtained results, the values of the maximum force ratio (MFR) were calculated. It could characterize the efficiency of bitumen modification by elastomer addition. Moreover, on the basis of the first tensile force maximum determined at 0 and 25°C, values of the maximum force index (MFI) were calculated. This parameter may be an alternative to commonly used penetration index.